Lymph node involvement: Positive about the role of the recurrence score in estrogen‐driven breast cancer?. Issue 2 (2nd November 2018) - Kalinsky, Kevin; O'Regan, Ruth M.
Abstract : It remains unclear whether there is clinical utility for withholding chemotherapy in HR+/HER2‐, node‐positive breast cancer based upon the 21‐gene Recurrence Score. While we await the results from randomized, phase III trials, this editorial addresses additional observational data that suggest there may be a role for this genomic assay in this patient population.